WOMEN’S STEREOTYPE AND MEN’S DOMINATION AS REFLECTED IN STEPHANIE MEYER’S THE TWILIGHT SERIES - Marisa Lovely (English Department, Faculty of Humanities, Andalas University, 2013)
ABSTRACTThis article analyses the Twilight Series by Stephanie Meyer. These novels tell about the relationship among human, vampire and werewolf. This research aims to identify the stereotype of women and men in the novels. The writer focuses the analysis on some of women characters and men characters by appling the theory from Cheri Register “prescriptive criticism”. Register has standard toward a literary works from feminist view point. After analyzing the data, the writer found three women’s stereotype and two men’s domination. The negative depiction potrays (1) Women as dependent beings, (2) Women as submissive beings and (3) women as less Intelectual beings. The writer assumes that the twilight series do not participate on feminist development eventhough the author is a woman.Keywords: feminist criticism, Prescriptive criticism, Twilight series